Epistemologi Fazlur Rahman dan Relevansinya dengan Model Pendidikan Pesantren Kontemporer - Habibi, Hasbi (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2022)
This study discusses the epistemological construction of Fazlur Rahman's thoughts regarding its relevance to the Islamic boarding school education model in the modern era. Until now, pesantren education is still faced with a problematic position between 'historical determinism' and 'practical realism'. In reality, pesantren education is still fascinated by the idealization of the golden age of the past Islamic civilization which was so hegemonic. On the other hand, pesantren education is also encouraged to be able to accept today's demands, especially those that come from Western ideas with a very practical orientation. Fazlur Rahman as an Islamic reformer has views on the historical journey of Islamic education, so he criticizes the traditionalization of knowledge in Islamic history with a neo-modernist style of thought. Fazlur Rahman's biggest contribution to Muslims is the overhaul of epistemological conceptions which has caused Muslim people's thinking to be old-fashioned, puritanical and dichotomous in solving problems, which has resulted in Muslims finding it difficult to think synthetically, elastically and pragmatically. In this case, Fazlur Rahman has provided an alternative way of thinking for Muslims in today's modern era, especially in the world of Islamic education.